Introduction to the Special Issue: Public Policy - Baker, Rachel; Jeffares, Stephen (Operant Subjectivity, 2013)
Today we are living in a world of ever-deepening shadow, in which basic democratic values are challenged as never before and in which even the survival of the human species is at stake. Under these circumstances it makes sense to develop a strategy of using our limited intellectual resources for the defense and extension of our values. The term ‘policy’ is used to indicate the need for clarifying the social ends to be served by a given allocation (including self-allocation) of scientific energy. (Lasswell, 1948, p. 122)